Pharmacokinetics and Dose Proportionality Study of a Novel Antiparkinsonian Agent, a 1H-1,2,4-Triazol-3-ylthio-conjugate of Prottremine - Daria S. Gorina; Anastasiya V. Lastovka; Artem D. Rogachev; Alexandra V. Podturkina; Alla V. Pavlova; Oleg V. Ardashov; Nikolai S. Li-Zhulanov; Tatyana G. Tolstikova; Konstantin P. Volcho; Nariman F. Salakhutdinov (Molecules)
The novel antiparkinsonian agent PA-96 is the focus of our research. PA-96 supported the survival of cultured naïve dopamine neurons, alleviated motor deficits in MPTP and haloperidol-based mice models of Parkinson’s disease, and increased the density of tyrosine hydroxylase positive neurons and dopamine concentration in the midbrain of an MPTP-damaged brain. In this work, an HPLC–MS/MS method was developed and validated, and the pharmacokinetics of the agent was investigated in mice after a single or multiple oral administration (p.o.) and intravenous injection (i.v.) at various doses. The dose proportionality was also evaluated after a single p.o. administration of three ascending doses (1, 5, and 10 mg/kg) and a single i.v. injection of two doses (1 and 10 mg/kg); also, the bioavailability was estimated. The disproportionality of pharmacokinetic parameters could be explained by the saturation of active centres of enzymes or receptors binding the substance: at low doses, part of the compound is bound, leaving a small amount circulating in blood, and rapidly metabolised and/or bound too. The bioavailability of PA-96 was c.a. 7 and 35% for the doses of 5 and 10 mg/kg, correspondingly.